Windows XP Hacks - Gralla, Preston (O'Reilly, 2011)
Now power users can rejoice! Windows XP Hacks offers tips, tools, and know-how to bend Windows XP to your will. The book delves into XP topics such as controlling the control panel, changing unchangeable icons, removing uninstallable XP components, stopping pop-up ads, taking a bite out of cookies, speeding up file downloads, protecting yourself with firewalls and proxy servers, and more. Users of both Windows XP Home Edition and Windows XP Pro Edition will find smart, timesaving, fun, and useful hacks for virtually every feature in their operating system. Even if you're not a power user yet, this book will have you well on your way.